New Report of Dysmicoccus brevipes Cockerell (1893) (Hemiptera: Pseudococcidae) on Heliconia sp., Lagenaria sp., and Zea mays L. Root in Bali Indonesia - I Putu Sudiarta; Komang Saraswati Devi; Gusti Ngurah Alit Susanta Wirya; Putu Shinta Devi; Febri Eka Wijayanti; Made Getas Pudak Wangi (Journal of Tropical Biodiversity and Biotechnology, 2025)
The pink pineapple mealybug, scientifically known as Dysmicoccus brevipes (Cockerell) (Hemiptera: Pseudococcidae), can associate with all part of the plant, including the roots. Additionally, it plays crucial role as a carrier of plant viruses, highlighting its importance in relation to host plants. Reports of D. brevipes infestations on above-ground plant parts in Indonesia have been documented since 1917. However, there is a lack of data on the infestation of subterranean plant parts or roots by this organism which highlights the significance of this research. This article presents the identification of mealybugs on the roots of Heliconia sp., Lagenaria sp., and Zea mays L. from Bali, Indonesia, using a morphological method based on determination keys by Williams (2004) and a molecular method based on the MtCOI gene. The findings of this study suggested that the species observed on all three host plants was D. brevipes, making it the most recent record of D. brevipes presence on Heliconia sp., Lagenaria sp., and Z. mays roots in Bali, Indonesia.